Making Audio Visible: The Lessons of Visual Language for the Textualization of Sound. - Bernstein, Charles (Textual Practice, 2009)
This essay presents considerations of the ontology of sound in recorded voice, in response to the implications for poetry of 100 years of voices on tape. The conjuring of voice unattached has a profound significance for poetry as a medium. The gramophone reverses the Jakobsonian definition of poetry: it incites the perception of mechanical sound as if it were speech. The gramophone is a reverse order poetry machine. The recorded voice only speaks; the possibility for dialogue or response always present at a reading - where the presence of an audience intimately affects what is being presented - is illusory, making our close listening across the electrostatic barrier all the more our own private affair. The recorded reading reenacts the conditions for dialogue without its actual presence, unless we want to consider the presence of the imagination. For the imaginative projection solicited by close listening to the gramophonic poemis the one writing has required all along. For teachers, one obvious implication of the archive of recorded poetry becoming more available is that listening to the poem read by the poet might become a commonplace feature in any course. The sound file would become, ipso facto, a text for study, much like the visual document. Another central issue is the effect that sound files might have on scholarly editions.